-2(1-5x)=-(x+1)

Simple and best practice solution for -2(1-5x)=-(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(1-5x)=-(x+1) equation:


Simplifying
-2(1 + -5x) = -1(x + 1)
(1 * -2 + -5x * -2) = -1(x + 1)
(-2 + 10x) = -1(x + 1)

Reorder the terms:
-2 + 10x = -1(1 + x)
-2 + 10x = (1 * -1 + x * -1)
-2 + 10x = (-1 + -1x)

Solving
-2 + 10x = -1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-2 + 10x + x = -1 + -1x + x

Combine like terms: 10x + x = 11x
-2 + 11x = -1 + -1x + x

Combine like terms: -1x + x = 0
-2 + 11x = -1 + 0
-2 + 11x = -1

Add '2' to each side of the equation.
-2 + 2 + 11x = -1 + 2

Combine like terms: -2 + 2 = 0
0 + 11x = -1 + 2
11x = -1 + 2

Combine like terms: -1 + 2 = 1
11x = 1

Divide each side by '11'.
x = 0.09090909091

Simplifying
x = 0.09090909091

See similar equations:

| 360+96k=0 | | -2(x+4)+5= | | x+2=7y | | 3x^2-12=0 | | 96=94p | | x-5/3=6 | | 50.50+18n= | | 2c+8=81 | | [2x+9]-10=5 | | -12-(x-3)=4x+5 | | 12+(3-2x)=-x | | X=(3)2 | | x^2+x+2=0 | | 12+(2x-3)=-x | | 3x^2-6y-39=0 | | 2x^2-2x-24=0 | | 3x^2-18x-39=0 | | 3x^2-18x+-9=0 | | (1/2x^5)6 | | 10y=-8x+5 | | -25=9+7(c-5) | | -2.30-0.60y=1.4 | | 2/9-8n^2 | | cos(2x)-3cos(x)+4=0 | | 20x-12y=28 | | 6s*39=141 | | 5x+13=6x | | 6s+39=141 | | 3(x+5)+2(x-3)=0 | | 2(1-4x)=-2(x+3)-4 | | 2-8x=-2x-6-4 | | -2.3+x=5.9 |

Equations solver categories